América Latina y el Acuerdo de París: sentando las bases para una gobernanza transnacional efectiva (Coyuntura) - Guzmán León, Alicia (2015)
Between 2010 and 2013, Latin America became indebt with six dollars for each dollar that had received as a donation for climate projects. New data (2013-2014) given by the Organization for Economic Co-operation and Development (OECD), showed that this relation has decreased to 3.6 dollars of credit for each dollar that has been donated. However, the omission of the contributions of developing countries persists in the source of information, so the amplitude of the financing gap is still unknown, as well as who is assuming the bill for the mitigation and adaptation of the phenomenon. This article examines the financial climate flows to the region, between 2010 and 2013, and the resources for the REDD+ mechanism. The aim is to draw the prevailing governance model in the region and to establish recommendations vis-à-vis the new Protocol.